Kedudukan Hukum Gambar yang Dihasilkan oleh Kecerdasan Buatan Sebagai Objek Jual Beli dalam Akta Notaris - Florencia Imanuelia Tania; Sahat Marulitua Sidabukke (Jurnal Hukum Lex Generalis, 2025)
The advancement of artificial intelligence (AI) technology opens new possibilities for images generated by AI to be used as objects in Notarial Sale and Purchase Deed. The images produced by AI are regarded as representations of human intellectual work due to the process of giving instructions and curation. Therefore, these images hold legal status as object of agreement in Notarial Sale and Purchase Deed, provided they comply with the applicable regulations in Indonesia.